2015
DOI: 10.3325/cmj.2015.56.24
|View full text |Cite
|
Sign up to set email alerts
|

Long-term angiographic outcome of stent-assisted coiling compared to non-assisted coiling of intracranial saccular aneurysms

Abstract: AimTo compare angiographic result at long-term follow-up, and rates of progressive occlusion, recurrence, and retreatment of stent-assisted coiled (SAC) and non-assisted coiled (NAC) intracranial saccular aneurysms.MethodsRetrospective evaluation of department records identified 260 patients with 283 saccular intracranial aneurysms who had long-term angiographic follow-up (more than 12 months) and were successfully treated with SAC (89 aneurysms) or NAC (194 aneurysms) at the University Hospital Center Zagreb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…More specifically, in the stent group, complete occlusion, neck remnant, and residual sac were noted in 46.3% (100/216), 19.0% (41/216), and 34.7% (75/216), respectively, compared with 63.5% (704/1109), 18.2% (202/1109), and 18.3% (203/1109) in the non-stent group. Ozretic et al 20 showed that only 36.0% (102/283) of aneurysms had complete occlusion. In particular, patients who underwent stent assisted coil embolization showed complete occlusion in 20%, residual neck in 15%, and residual sac in 65%.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, in the stent group, complete occlusion, neck remnant, and residual sac were noted in 46.3% (100/216), 19.0% (41/216), and 34.7% (75/216), respectively, compared with 63.5% (704/1109), 18.2% (202/1109), and 18.3% (203/1109) in the non-stent group. Ozretic et al 20 showed that only 36.0% (102/283) of aneurysms had complete occlusion. In particular, patients who underwent stent assisted coil embolization showed complete occlusion in 20%, residual neck in 15%, and residual sac in 65%.…”
Section: Discussionmentioning
confidence: 98%
“…17 Ozretic´et al also reported that SAC did not reduce the rate of recurrence and retreatment. 19 Tight coil packing is, therefore, desirable, even when stents are adjunctively placed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that aneurysms treated with SAC were less prone to recurrence, 3,5,8,[10][11][12] while other studies did not show such an effect. 4,6,7,9 Higher treatment-related risks of mortality and morbidity were shown in some reports, 3,7,11 but not in others. [4][5][6]8,10 Many studies reported significant baseline differences between the groups being compared, most often with characteristics that could favor SAC (ie, a high proportion of unruptured sidewall aneurysms and shorter follow-up time).…”
Section: Stent Placement and Residual Aneurysmsmentioning
confidence: 93%
“…3,[6][7][8][10][11][12][37][38][39][40] This hypothesis has never been tested in a randomized trial. Previous studies, [3][4][5][6][7][8][9][10] including systematic reviews and meta-analyses, 11,12 have shown diverging results. Some studies have reported that aneurysms treated with SAC were less prone to recurrence, 3,5,8,[10][11][12] while other studies did not show such an effect.…”
Section: Stent Placement and Residual Aneurysmsmentioning
confidence: 95%
See 1 more Smart Citation